2000
DOI: 10.1086/318118
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use and Colonization with Erythromycin‐ResistantStreptococcus pneumoniaein Greece during the First 2 Years of Life

Abstract: We evaluated nasopharyngeal colonization with erythromycin-resistant Streptococcus pneumoniae during the first 2 years of life in central and southern Greece. Of 2448 children studied from February 1997 to February 1999, 766 (31%) carried 781 pneumococcal isolates. Ninety-five (3.9%) of the children attended day care centers. Eighteen percent of the pneumococci were resistant to erythromycin (minimal inhibitory concentration 1 to >128 microg/mL), with 67.9% of them carrying the erm(B) gene and 29.2% mef(A) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 43 publications
0
51
0
2
Order By: Relevance
“…We studied a collection of 128 S. pneumoniae isolates susceptible to penicillin but resistant to erythromycin and/or other non-␤-lactam agents; the isolates were recovered from nasopharyngeal cultures obtained from children during two independent studies in Greece (3,30,31). The first study was performed in 338 children attending seven day care centers in the city of Patras in southwestern Greece during the 2-month period from December 1995 to February 1996.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied a collection of 128 S. pneumoniae isolates susceptible to penicillin but resistant to erythromycin and/or other non-␤-lactam agents; the isolates were recovered from nasopharyngeal cultures obtained from children during two independent studies in Greece (3,30,31). The first study was performed in 338 children attending seven day care centers in the city of Patras in southwestern Greece during the 2-month period from December 1995 to February 1996.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…Isolation, identification, and susceptibility testing of the Greek S. pneumoniae isolates were performed by applying standard methods as described previously (30,31). Penicillin and erythromycin MICs for the Greek isolates were determined by the E-test method (AB Biodisk, Solna, Sweden).…”
Section: Bacterial Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, risk factors for the carriage of resistant S. pneumoniae have been well investigated in the last couple of decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and those studies reported that the most influencing factor was the previous use of antibiotics. Unnecessary use of antibiotics had been thought to cause this emergence of antibiotic resistant S. pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of genes coding for macrolide resistance was studied by PCR as described previously (8,12,13 (14,15), were evaluated for their susceptibility to 10 antibiotics representing different classes of antimicrobial agents. These agents were 14-member (erythromycin and clarithromycin), 15-member (azithromycin), and 16-member ring macrolides (miocamycin), lincosamides (clindamycin), streptogramins (quinupristin/dalfopristin), ketolides (telithromycin), penicillin G, tetracycline, and chloramphenicol.…”
mentioning
confidence: 99%